(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Akhbar, Naharuddin, Arianingsih I, Misrah, Akhbar RK. 2022. Spatial model of forest area designation and function based on multi-criteria in dry land and mangrove forest ecosystems, Central Sulawesi, Indonesia. Biodiversitas 23: 3620-3630. Along with the dynamics of rapid social change and the need for land for economic development, land and climate parameters on changes in the designation and function of forest areas, it is time to integrate with socio-economic parameters and government policies while still paying attention to the condition of existing forest vegetation cover. This study aimed to develop a spatial analysis model of changes in the designation and function of forest areas based on multi-criteria in dry land and mangrove forest ecosystems. The research used a descriptive-spatial method with a multi-criteria-based decision-making technique for changes in the designation and function of forest areas. The data analysis utilizes Geographic Information System. The motivation for the proposed forest area change is the target to be achieved in the multi-criteria decision analysis. This research resulted in a spatial analysis approach that integrates scoring techniques and multi-criteria-based decision-making techniques. In Locus BL_010, a change in the function of forest area can be generated, while in Locus TL_003 a decision is made to change the allocation and function of forest area. The achievement of multi-criteria-based spatial analysis on changes in the designation and function of forest areas is quite flexible in decision making because each proposed motivational target will be achieved if it is in accordance with the established criteria and field facts.